Performance of motor imitation in children with and without dyspraxia - Korrawan Ruttanathantong (2018)
Background: Motor imitation is truly essential for young children to learn new motor skills, social behavior, and skilled acts or praxis. The present study aimed to investigate motor imitation ability between typically-developing children and dyspraxic children and to examine the development trends in both children groups. Material and Method: The comparison of motor imitation was studied in 55 typically-developing children and 59 dyspraxic children aged 5 to 8 years. The Motor Imitation subtest consisted of two sections, imitation of postures and imitation of verbal instructions. Typically-developing children and dyspraxic children were examined for developmental trends. The independent samples t-test was used to analyze the differences between both groups. Two-way analysis of variance (ANOVA) was used to analyze inter-age differences for each age group. Results: The results revealed significant differences between dyspraxic and typically-developing children. Both typically-developing and dyspraxic children demonstrated age trends. The older children scored higher than younger children. Conclusion: Imitation is a primary learning strategy of young children. It is essential that children with dyspraxia receive early detection and need effective intervention. Typically-developing children and dyspraxic children showed higher mean score on the Imitation of Posture section than the Verbal Instructions section. Motor imitation competency, therefore, changes and improves with age.